Le devoir d’enfant à l’ère de la médicalisation : stigmates, retournements et brèches en procréation assistée - Laurence Tain (Genre, Sexualité et Société)
This contribution focuses on the social treatment of the childbearing duty, the stigma it can produce, as well as the paradoxes of this duty. In every society, women escaping the reproductive injunction are stigmatized in a peculiar way. Currently, the medical institution plays a major role in this process.  Observing medicalized trajectories is a potent prism through which the mechanisms and the contradictions of this social regulation can be grasped. Many women do not follow the reproductive heterosexuality norm along their life course – women who don’t want children, lesbian women who want to have children -- This article offers to study the trajectories of women resorting to reproductive technologies. First, we show how the medical institution contributes to stigmatize infertility and to anticipate medical resort. Nethertheless, if some trajectories obey these injunctions, others desobey to them. Consequently, gaps are being opened in the reproductive heterosexuality norm. We could then wonder which social or national properties  explain the obedience to these norms.